2023
DOI: 10.3390/ijms24087184
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cardioprotective Antidiabetic Therapy on Microbiota in Patients with Type 2 Diabetes Mellitus—A Systematic Review

Abstract: As the pathophysiologic mechanisms of type 2 diabetes mellitus (T2DM) are discovered, there is a switch from glucocentric to a more comprehensive, patient-centered management. The holistic approach considers the interlink between T2DM and its complications, finding the best therapies for minimizing the cardiovascular (CV) or renal risk and benefitting from the treatment‘s pleiotropic effects. Sodium-glucose cotransporter 2 inhibitors (SGLT-2i) and glucagon-like peptide-1 receptor agonists (GLP-1 RA) fit best i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Conversely, SGLT2 inhibitors and TZDs have been suggested to have less pronounced effects on gut microbiota and microbial metabolites compared to other treatments [ 124 ]. Although the exact microbial patterns linked to individual antidiabetic drugs are unknown, understanding how these treatments affect the gut microbiota might be essential in identifying their potential mechanisms and improving their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, SGLT2 inhibitors and TZDs have been suggested to have less pronounced effects on gut microbiota and microbial metabolites compared to other treatments [ 124 ]. Although the exact microbial patterns linked to individual antidiabetic drugs are unknown, understanding how these treatments affect the gut microbiota might be essential in identifying their potential mechanisms and improving their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al demonstrated that treatment with Dapagliflozin can reduce the Firmicutes:Bacteroidetes ratio and increased the Akkermansia muciniphila population [174]. Treatment with Empagliflozin increases SCFA-producing species, such as Eubacterium, Roseburia, and Faecalibacterium [176]. However, dapagliflozin concurrently elicits potential side effects.…”
Section: The Role Of Gm Modulation In the Gut-kidney-heart Axismentioning
confidence: 99%
“…Furthermore, metformin inhibits fructose-1,6-bisphosphatase by a hepatic AMPK-independent mechanism [33]. It changes the composition of the microbiota [5], thus reducing inflammation. In addition, it downregulates the expression of genes encoding pro-inflammatory cytokine production [15], significantly decreasing excessive inflammatory responses and thus slowing disease progression [4].…”
Section: • Metforminmentioning
confidence: 99%
“…These figures indicate that diabetes is causing high mortality rates globally, hence the need for requisite interventions to handle the growing number of affected individuals worldwide [4]. Diabetes leads to non-traumatic lower extremity amputations, end-stage renal disease, and adult-onset blindness [5]. These complications cause severe disabilities and chronic disorders [2] among affected individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation